Inherently Chiral Upper-Rim-Bridged Calix[4]arenes Possessing a Seven Membered Ring - Tlustý, Martin; Slavík, Petr; Kohout, Michal; Eigner, Václav; Lhoták, Pavel (Organic letters, 2017)
The mercuration of calix[4]arene immobilized in the cone conformation allowed the introduction of an amino group at the meta position of the basic skeleton. Acylation and subsequent intramolecular Bischler-Napieralski-type cyclization led to a novel type of bridged calixarene containing a seven-membered ring. These compounds with an enlarged and rigidified cavity represent a unique and inherently chiral system that may potentially be applicable for the design of chiral receptors. The absolute configuration of one enantiomer, obtained by resolution of the racemate using chiral HPLC, was assigned by single-crystal structure determination.